Analisis Kepuasan Pengguna Sistem Informasi Keuangan Blu Di Universitas Negeri Gorontalo Menggunakan Model EUCS - Musa, Viviwidyawati A; Amali, Lanto Ningrayati; Tuloli, Mohamad Syafri; Katili, Muhammad Rifai; Hadjaratie, Lillyan; Padiku, Indhitya R (Gorontalo State University, 2024)
The SIKBLU application was created with the aim of being an information system media for employees. SIKBLU is an information system in the form of a web application which is an internal product of the Gorontalo State University information system which is useful for supporting financial management activities. SIKBLU is used to support employee work regarding financial management, but in implementing the SIKBLU application problems often occur such as the system portal link not being accessible when an update occurs to the system. This can affect the user's work or the user's ability to complete work. This research was conducted to determine the extent of user satisfaction with the Gorontalo State University information system (SIKBLU), and what factors influence user satisfaction. This research uses descriptive quantitative methods and uses the EUCS model to measure the level of user satisfaction. The results of the analysis show that the content variable has a positive effect on user satisfaction, the accuracy variable has a positive effect on user satisfaction, the user convenience variable has no positive effect on user satisfaction, the form variable has no positive effect on user satisfaction, and the time variable has no positive effect on user satisfaction. The user satisfaction level reaches 83% and is in the good category.